Biodistribution Analysis of an Anti-EGFR Antibody in the Rat Brain: Validation of CSF Microcirculation as a Viable Pathway to Circumvent the Blood-Brain Barrier for Drug Delivery - Ghazal Naseri Kouzehgarani; Pankaj Kumar; Susan E. Bolin; Edward B. Reilly; Didier R. Lefebvre (Pharmaceutics, 2022)
Cerebrospinal fluid (CSF) microcirculation refers to CSF flow through brain or spinal parenchyma. CSF enters the tissue along the perivascular spaces of the penetrating arteries where it mixes with the interstitial fluid circulating through the extracellular space. The potential of harnessing CSF microcirculation for drug delivery to deep areas of the brain remains an area of controversy. This paper sheds additional light on this debate by showing that ABT-806, an EGFR-specific humanized IgG1 monoclonal antibody (mAb), reaches both the cortical and the deep subcortical layers of the rat brain following intra-cisterna magna (ICM) injection. This is significant because the molecular weight of this mAb (150 kDa) is highest among proteins reported to have penetrated deeply into the brain via the CSF route. This finding further confirms the potential of CSF circulation as a drug delivery system for a large subset of molecules offering promise for the treatment of various brain diseases with poor distribution across the blood-brain barrier (BBB). ABT-806 is the parent antibody of ABT-414, an antibody-drug conjugate (ADC) developed to engage EGFR-overexpressing glioblastoma (GBM) tumor cells. To pave the way for future efficacy studies for the treatment of GBM with an intra-CSF administered ADC consisting of a conjugate of ABT-806 (or of one of its close analogs), we verified in vivo the binding of ABT-414 to GBM tumor cells implanted in the cisterna magna and collected toxicity data from both the central nervous system (CNS) and peripheral tissues. The current study supports further exploration of harnessing CSF microcirculation as an alternative to systemic delivery to achieve higher brain tissue exposure, while reducing previously reported ocular toxicity with ABT-414.